Three subsets of genes whose tissue specific expression is sex and age-dependent can be identified within the rat alpha(2u)-globulin family - Wang, Kathy S.; McFadyen, David A.; Locke, John; Hodgetts, Ross B. (My University, 1997)
The rat α2u‐globulins are encoded by a multigene family whose 20–25 members are subjected to multihormonal regulation that is dependent upon the sex of the animal, the developmental stage and the tissue being examined. Using RT‐PCR and diagnostic restriction analysis of the products, we have examined the specificity of the expression of different members of the gene family. All family members can be classified into three subsets, depending on how the amplified cDNA responds to digestion with ApaLI, SstI and VspI. Subset A contains the restriction sites for both ApaLI and SstI but not VspI and typifies the genes expressed in the salivary glands of both mature and juvenile animals of both sexes, where it is the only subset expressed. This subset of genes also accounts for all the transcripts observed in the kidneys and mammary glands of juvenile males. Although subset A was represented in the transcript populations of all the other tissues examined, its proportion relative to the total varied greatly. The two other subsets were subset V, which contains only the restriction site for VspI, and subset N, which lacks all three restriction sites. In all the other tissues examined, two or all three of the subsets were expressed, usually in a manner that was unique to the sex and age of the tissue in question. The proportion of each of the three α2u‐globulin subsets in the α2u‐globulin gene family was determined by quantitation of the restriction products of amplified genomic DNA. Interestingly, the most prevalent subset in the genome (N) has the most limited tissue expression pattern, but is found in liver and preputial glands, the tissues expressing the most substantial quantities of α2u‐globulin. These results indicate the complexity of the regulation of the α2u‐globulins and point to the necessity for gene specific analyses if the expression of the family is to be understood in molecular terms.
Keywords: rat α2u‐globulin; multigene family; tandem gene array; RT‐PCR